Prevalence of child marriage and associated factors among reproductive age women in Harari regional state, eastern Ethiopia, 2022: a community-based study - Magarsa Lami; Abraham Negash; Addis Eyeberu; Abdi Birhanu; Adera Debella; Tamirat Getachew; Bekelu Berhanu; Bikila Balis; Tilahun Bete; Tilahun Abdeta; Shambel Nigussie; Kasahun Bogale; et al. (BMC, 2023)
Abstract Introduction Child marriage is a union before the age of 18 and a violation of human right. Around 21% of young women in the world married before reaching the age of 18. Every year, 10 million girls under the age of 18 are married. Child marriage causes lifetime suffering, and its abolition was one component of the Sustainable Development Goal to achieve gender equality and empower women and girls. However; abolition of child marriage by 2030 will not happen because its prevalence in the community has remained stable. Objective To assess the prevalence of child marriage and its associated factors among reproductive-age women from March 7 to April 5, 2022 in Harari Regional State, eastern Ethiopia. Methods Community-based cross-sectional study was conducted from March 7 to April 5, 2022 among the reproductive age group in the Harari Region state, Eastern Ethiopia. A systematic random sampling technique was used to find study participants. Data were obtained by face-to-face interview using a pre-tested structured questionnaire, input into EpiData version 3.1 and analyzed using Stata version 16. The proportion with 95% confidence interval (CI) and the summery measure were used to report the prevalence. A multivariable logistic regression analysis model was used to examine associated factors, and the results were provided as an adjusted odds ratio (AOR) with a 95% confidence interval. Result In this study 986 were responded to the interview, making response rate of 99.6%. The median age of study participants was 22 years. The prevalence of child marriage was 33.7% [95% CI: 30.8-36.7] in this study. Being a Muslim (AOR = 2.30, 95% CI = 1.26, 4.19), diploma or higher level of education (AOR = 0.26, 95%CI = .10, 0.70), rural residence (AOR = 5.39, 95% CI = 3.71, 7.82), a marriage arranged by others (AOR = 2.68, 95% CI = 1.49, 4.82) and not knowing legal age of marriage (AOR = 4.49, 95% CI = 2.57, 7.85) were significantly associated with child marriage. Conclusion According to this report, nearly one out of every three women engages in child marriage. The practice was more common among those with lower educational attainment, those who lived in rural areas, people who were unaware of the legal age of marriage, and those whose engagement was decided by others. Focusing on strategies that allow for intervention in these factors is beneficial in ending child marriage, which has a direct and indirect impact on women's health and educational achievement.